Remarkably Selective Formation of Allenyl and Dienyl Alcohols via Ni-Catalyzed Coupling Reaction of Conjugated Enyne, Aldehyde, and Organozinc Reagents - Mori, Yasuyuki; Kawabata, Toshiki; Onodera, Gen; Kimura, Masanari (Synthesis, 2016)
A nickel catalyst promotes the multi-component reactions (MCRs) of conjugated enynes, aldehydes, and organozinc reagents to form unsaturated alcohols. Ligand effects dramatically control the regioselectivity in these Ni-catalyzed MCRs, leading to the selective formation of allenyl alcohols and conjugated dienyl alcohols.
Keywords: nickel; multi-component reaction; organozinc reagent; conjugated enyne; allenyl alcohol; dienyl alcohol